Refractary Medical Epilepsy: Treatment and Follow-up with Schmidt’s Scale (1997)
ABSTRACT: Epilepsy tre&d adequately bur with persistenr seizures is termed refractory epilepsy. Schmidt’s scale differentiates refractory epilepsy from inadequately treated epilepsy. We report the clinical characteristics of patients with refractory epilepsy, as well as the seizure evolution according to Schmidt’s pharmacologic scale. Between February and November 1996, we made a prospective follow-up of 15 patients with four or more seizures a month who were receiving antiepileptic drug (AED) treatment. The patients had the following clinical characteristics associated with refractory epilepsy: early age at onset and long duration of the epileptic illness, absence of idiopathic etiology, epileptic syndromes difficult to treat medically, mental handicap, and polytherapy. At first evaluation, Schmidt’s scale identified 60% (9 patients) as undertreated; at the last evaluation, 20% (3 patients) remained in that category. In a mean of 6.6 months, with changes effected in AED regimen, seizure frequency was reduced in 77.9%. In epileptic referral centers, a pharmacologic evaluation scale is recommended to optimize AED treatment in patients considered refractory to therapy. Schmidt’s scale differentiates inadequately treated patients and selects patient with refractory epilepsy as candidates for new AED trials or epileptic surgery.